Answer:
(x + 1)^2 + (y - 1)^2 = 74
Explanation:
By looking at the graph, we can see the center of the circle is (-1, 1).
Next, we can find the radius. We are given the point (6, -4) is on the circle. The distance from the center to a point on a circle is the radius. We can plug the points (-1, 1) and (6, -4) into the distance formula to get the radius:
r = √([-1-6]^2 + [1-(-4)]^2)
r = √(49 + 25)
r = √74
The equation of a circle is denoted in the form:
(x - h)^2 + (y - k)^2 = r^2
where (h, k) is the center and r is the radius.
We can plug in the values we calculated:
(x + 1)^2 + (y - 1)^2 = 74